2021
DOI: 10.1101/2021.02.08.21251339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multivariate spatio-temporal analysis of the global COVID-19 pandemic

Abstract: The Covid-19 pandemic has caused significant mortality and disruption on a global scale not seen in living memory. Understanding the spatial and temporal vectors of transmission as well as similarities in the trajectories of recorded cases and deaths across countries can aid in understanding the benefit or otherwise of varying interventions and control strategies on virus transmission. It can also highlight emerging globa trends as they occur. Data on number of cases and deaths across the globe have been made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the study by Xiang & Swallow [ 5 ], the authors analysed data from global trends relating to reported cases of, and deaths resulting from, SARS-CoV-2. Their analyses found that a single temporal trend dominated the global spread of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the study by Xiang & Swallow [ 5 ], the authors analysed data from global trends relating to reported cases of, and deaths resulting from, SARS-CoV-2. Their analyses found that a single temporal trend dominated the global spread of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…a univariate x. As in the study by Xiang & Swallow [5], this aims to remove trends specific to each stream, with residual variation used to determine the PCs. Remaining correlation in the model residuals between time [1, .…”
Section: Methods (A) Principal Components Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Between-country comparisons often receive significant backlash from politicians and the media and can easily be open to criticism for not accounting for some underlying process that has not been considered (demographic or environmental differences, for example) (Pearce et al, 2020;Xiang and Swallow, 2021;Komarova et al, 2020). Data collection procedures also vary drastically between nations and privacy constraints make large-scale analyses challenging to complete.…”
Section: Challenges In Parameter Estimation and Model Fittingmentioning
confidence: 99%